Sensitivity and specificity of vessel wall MRI sequences to diagnose central nervous system angiitis - Ferlini, Lorenzo; Ligot, Noemie; Rana, Arab; Jodaitis, Lise; Sadeghi, Niloufar; Destrebecq, Virginie; Naeije, Gilles (Frontiers in Stroke, 2022)
Magnetic resonance imaging (MRI) with intracranial vessel wall (IVW) sequences is able to directly characterize disease processes affecting the VW increasing the accuracy of intracranial vasculopathies differential diagnosis. Nevertheless, data concerning the specificity and sensitivity of this technic for diagnosis of angiitis of the central nervous system (ACNS) are scant. We aimed at quantifying the IVW abnormalities in a cohort of primary and secondary ACNS and assessing the specificity of ACNS-associated IVW MRI abnormalities. We retrospectively included thirty-six patients with a diagnosis of ACNS with IVW imaging and we compared IVW MRI abnormalities with those of fifty successive patients admitted at the stroke unit for acute neurological deficit (stroke-unit-group). Since an ACNS was retained as cause of the acute neurological deficit in two patients in the stroke-unit-group, they were finally included in the ACNS group. In our cohort, headache and cognitive disorders were present in 29 and 55% of cases respectively, seizure were rare (n = 5, 13%). CSF analysis were abnormal in 29 patients (76%). MRI showed lesion with restricted diffusion in 82% of patients (n = 31). In 71% of our ACNS population (n = 27) multifocal vessel abnormalities were described in angiographic MRI sequences. Digital subtraction angiography (DSA) was performed in 14 patients and it was suggestive of an ACNS in 11 (79%). Brain-meningeal biopsy was performed in two cases (5%). The typical ACNS-associated IVW abnormalities, i.e. the multifocal concentric VW enhancement with wall thickening, was found in the 95% of ACNS patients (n = 36) whereas it was reported in 4% (n = 2) of the stroke-unit-group (specificity and sensitivity of concentric VW enhancement for ACNS diagnosis of 95% and 94% respectively). IVW enhancement co-localized with multifocal angiographic stenosis in ACNS patients. The clinical, laboratory and imaging findings were comparable to those of previously described ACNS cohorts in the literature, and particularly to those of DSA-diagnosed patients. Our results suggest that concentric VW enhancement could efficaciously identify patients affected by medium-sized vessels CNS vasculitis with a specificity of 95% and sensitivity of 94%. Further studies with larger samples are necessary to confirm our findings.